Multiline variety for blast resistance - CGIAR Research Program on Rice (2019)
Near isogenic lines (NILs) for true blast resistance genes were developed (Pii, Pi3, Pik, Pik-h, Pikp, Pi1, Pi7(t), Piz, Piz-5, Pi9(t), Pi12(t), Pish). Genetic improvement of resistance was confirmed by inoculation test. To develop NILs for partial resistance genes (pi21 and PB1), hybrid populations (BC5F2 and BC6F2) were generated